1999
DOI: 10.1067/msy.1999.98741
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hospital volume and late survival after pancreaticoduodenectomy

Abstract: Hospital volume strongly influences both perioperative risk and long-term survival after pancreaticoduodenectomy. Our data suggest that both patient selection and differences in quality of care may underlie better outcomes at high-volume referral centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
125
3
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(138 citation statements)
references
References 0 publications
3
125
3
7
Order By: Relevance
“…The overall mortality ranges between 2-3% in specialised centres. Studies have shown that this low mortality is attributable to high volume centres with dedicated hepatobiliary surgery units, while the rate continues to be high in other hospitals [4][5][6]. Surgical skills and the experience of the surgeon has been found vital as it is directly linked with the overall mortality and post operative morbidity associated with this procedure [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The overall mortality ranges between 2-3% in specialised centres. Studies have shown that this low mortality is attributable to high volume centres with dedicated hepatobiliary surgery units, while the rate continues to be high in other hospitals [4][5][6]. Surgical skills and the experience of the surgeon has been found vital as it is directly linked with the overall mortality and post operative morbidity associated with this procedure [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, based on data from population-based cancer registries in the US, several studies have documented a significant relationship between hospital volume and survival. [1][2][3] In these studies, hospital volume is defined as the number of surgical operations for cancer performed at a hospital. However, no study has been conducted regarding the relationship between hospital volume of operations for cancer and survival using population-based data in Japan.…”
mentioning
confidence: 99%
“…Over the last two decades, a dramatic improvement in operative mortality after pancreaticoduodenectomy (PD) and pylorus-preserving pancreaticoduodenectomy (PPPD) has been observed for pancreatic and periampullary adenocarcinomas, especially in high-volume centers [1,2]. Better choice of adjuvant therapy has also improved survival in small number of patients.…”
Section: Introductionmentioning
confidence: 99%